Diagnosis of Horner's syndrome in dogs and cats. Issue 3 (5th March 2015) - Penderis, Jacques
Abstract : Horner's syndrome is a common condition in veterinary patients, particularly in dogs and cats, presenting with the typical features of miosis, enophthalmos, protrusion of the third eyelid and ptosis. It results from lesions affecting the sympathetic supply to the head and orbit. This article discusses what causes Horner's syndrome and how to diagnose the condition.